2016
DOI: 10.1103/physrevlett.117.266803
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Conformal Symmetry and Geometric Transport Properties of Quantum Hall States on Singular Surfaces

Abstract: We study quantum Hall states on surfaces with conical singularities. We show that a small parcel of electronic fluid at the cone tip gyrates with an intrinsic angular momentum whose value is quantized in units of the Planck constant and exists solely due the gravitational anomaly. We show that quantum Hall states behave as conformal primaries near singular points, with a conformal dimension equal to the angular momentum. We argue that the gravitational anomaly and conformal dimension determine the fine structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 45 publications
(121 reference statements)
3
56
0
Order By: Relevance
“…TINCs and junctions thereof could act as building blocks for more complex 3D mesoscopic setups for Dirac electrons -much as quantum point contacts and AB rings are used for planar setups -in particular for hybrid TIsuperconducting systems typically used in the search for Majorana fermions [9,38,39]. TINCs can also be seen as building units of arbitrarily shaped TINWs [29], where more exotic aspects of QH physics on curved surfaces can be studied [40,41]. Indeed, in Ref.…”
mentioning
confidence: 99%
“…TINCs and junctions thereof could act as building blocks for more complex 3D mesoscopic setups for Dirac electrons -much as quantum point contacts and AB rings are used for planar setups -in particular for hybrid TIsuperconducting systems typically used in the search for Majorana fermions [9,38,39]. TINCs can also be seen as building units of arbitrarily shaped TINWs [29], where more exotic aspects of QH physics on curved surfaces can be studied [40,41]. Indeed, in Ref.…”
mentioning
confidence: 99%
“…Geometry can also induce a reminiscent of the Hall effect [5]. Related important investigations can also be found in the literature, for instance: the quantum Hall effect near conical singularities [6] and investigations taking into account the Pauli equation for a charged spin particle on a curved surface with externally applied fields [7,8]. Recent developments can also be found in [9,10,11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The version for a curved non-interacting 2DEG in the presence of an electric and magnetic field was investigated in [7], where it was showed that no coupling between the fields and the quantum geometric potential arises. An application in this case can be viewed in [9], where important features concerned to the quantum Hall states on surfaces with conical singularities has been presented. The version for Pauli equation for a charged spin particle on a curved surface in an electric and magnetic field has been addressed in [10].…”
Section: Introductionmentioning
confidence: 99%